Efficient Bargains in the Context of Recent Labour Market Experience and Policy - Robert A. Hart; Thomas Moutos (W.E. Upjohn Institute for Employment Research, 1990)
In Europe in recent times, bargaining between a leading nationally-based industrial union and a representative group of employers over the issues of employment, wages and working time has proved to be influential in a much wider industrial context. Adopting a generalized Nash bargaining approach, this paper considers the possible effects on such "key" bargains of several prominent labor market events and policies experienced since the middle 1970s. These include the impacts of OPEC supply shocks, changes in union power, greater emphasis on payroll taxes as well as growing government economic orthodoxy as expressed through the goal of a balanced budget.
Keywords: J0; J5; 330; unions; Europe; bargaining; Moutos; Hart